Transforming rural agriculture with improved seed and mechanization - Shiela Chikulo; Kudzanai Chimhanda (International Maize and Wheat Improvement Center, 2024)
Attended by over 1,300 smallholder farmers, the fourth edition of the CIMMYT seed and mechanization fairs held in Mwenezi and Masvingo districts linked farmers with private sector companies.